Retroviral vectors displaying functional antibody fragments. - Russell, S J (1993)
We have made retrovirus particles displaying a functional antibody fragment. We fused the gene encoding an antibody fragment directed against a hapten with that encoding the viral envelope protein (Pr80env) of the ecotropic Moloney murine leukemia virus. The fusion gene was co-expressed in ecotropic retroviral packaging cells with a retroviral plasmid carrying the neomycin phosphotransferase gene (neo), and retroviral particles with specific hapten binding activities were recovered. Furthermore the hapten-binding particles were able to transfer the neo gene and the antibody-envelope fusion gene to mouse fibroblasts. In principle, the display of antibody fragments on the surface of recombinant retroviral particles could be used to target virus to cells for gene delivery, or to retain the virus in target tissues.